2022
DOI: 10.1021/acsami.2c06699
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Flexible Thin-Film Encapsulant with Sandwich Structures of Perhydropolysilazane Layers

Abstract: Perovskite solar cells (PSCs) have attracted considerable attention due to their excellent photovoltaic properties, but stability issues have prevented their widespread application. PSCs must be protected by encapsulation to extend their lifetime. Here, we show that perhydropolysilazane (PHPS)-based multilayered encapsulation improves the lifetime of PSCs. The PSCs were encapsulated by converting PHPS into silica under vacuum ultraviolet (UV) irradiation. The PHPS-based multilayer encapsulation method achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Compared to the conventional glass cover encapsulation technique, thin film encapsulation possesses distinguished Recently, Dr. Nochang Park and colleagues at Korea Electronics Technology Institute developed a low-cost solution-processed flexible multi-layer encapsulation method and demonstrated excellent WVTR as well as PV cell lifetime when applied to encapsulate perovskite solar cells (Kim et al, 2022). They used perhydropolysilazane (PHPS), which consists of −SiH2−NH− backbone, as a precursor solution to form SiO x -SiON x barrier layer on a flexible poly (ethylene terephthalate) (PET) film.…”
Section: Spotlight In Plasmonicsmentioning
confidence: 99%
“…Compared to the conventional glass cover encapsulation technique, thin film encapsulation possesses distinguished Recently, Dr. Nochang Park and colleagues at Korea Electronics Technology Institute developed a low-cost solution-processed flexible multi-layer encapsulation method and demonstrated excellent WVTR as well as PV cell lifetime when applied to encapsulate perovskite solar cells (Kim et al, 2022). They used perhydropolysilazane (PHPS), which consists of −SiH2−NH− backbone, as a precursor solution to form SiO x -SiON x barrier layer on a flexible poly (ethylene terephthalate) (PET) film.…”
Section: Spotlight In Plasmonicsmentioning
confidence: 99%
“…To date, many efforts have been made to strengthen the long-term stability of PSCs. Besides improving the stability of the perovskite, charge-transporting materials, and electrodes, protecting the PSCs with robust barriers/encapsulation is also important to improve the stability of PSCs. , For example, McGehee et al reported the use of ethylene vinyl acetate (EVA)-based cover encapsulation in PSCs, and the encapsulated solar cells can withstand temperature cycles from −40 to 85 °C . Later, Han et al compared three kinds of adhesives, that is, polyurethane (PU), polyolefin, and EVA.…”
Section: Introductionmentioning
confidence: 99%
“…materials based on nano-clays [19] or glass flakes, [20] perhydropolysilazane (PHPS) has been used as printed encapsulant due to its high capability of blocking the ingress of moisture and oxygen. [10,[21][22][23][24] PHPS is a nontoxic and low-cost material that is also widely used as barrier coating for passivating steel or silicon surfaces (including photovoltaics). [25][26][27][28] The backbone of this inorganic polymer class consists of silicon and nitrogen atoms (SiNH 2 -NH) and thus can be converted to silica by exposure to water vapor or reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] In addition to composite materials based on nano‐clays [ 19 ] or glass flakes, [ 20 ] perhydropolysilazane (PHPS) has been used as printed encapsulant due to its high capability of blocking the ingress of moisture and oxygen. [ 10,21–24 ]…”
Section: Introductionmentioning
confidence: 99%